Vector competence of Malaysian Aedes albopictus with and without Wolbachia to four dengue virus serotypes. Issue 9 (17th July 2017) - Joanne, Sylvia; Vythilingam, Indra; Teoh, Boon‐Teong; Leong, Cherng‐Shii; Tan, Kim‐Kee; Wong, Meng‐Li; Yugavathy, Nava; AbuBakar, Sazaly
Abstract: Objective: To determine the susceptibility status of Aedes albopictus with and without Wolbachia to the four dengue virus serotypes. Methods: Two newly colonised colonies of Ae. albopictus from the wild were used for the study. One colony was naturally infected with Wolbachia while in the other Wolbachia was removed by tetracycline treatment. Both colonies were orally infected with dengue virus‐infected fresh blood meal. Dengue virus load was measured using quantitative RT‐PCR at four‐time intervals in the salivary glands, midguts and ovaries. Results: Wolbachia did not significantly affect Malaysian Ae. albopictus dengue infection or the dissemination rate for all four dengue virus serotypes. Malaysian Ae. albopictus had the highest replication kinetics for DENV‐1 and the highest salivary gland and midgut infection rate for DENV‐4. Conclusion: Wolbachia, which naturally exists in Malaysian Ae. albopictus, does not significantly affect dengue virus replication. Malaysian Ae. albopictus is susceptible to dengue virus infections and capable of transmitting dengue virus, especially DENV‐1 and DENV‐4. Removal of Wolbachia from Malaysian Ae. albopictus would not reduce their susceptibility status.